'De-mockery-cy' and the Discourse of Human Rights in Ngugi wa Thiong'o's Wizard of the Crow - Ruma, Mustapha Bala (SARE: Southeast Asian Review of English, 2017)
Wizard of the Crow (2007) is important in Ngugi's oeuvre because it signifies a departure from his earlier political positions. Not only did the novel come out after two decades or so of inactivity in his novelistic production since Matigari (1988), it was also initially composed in Gikuyu as Murogi wa Kagogo twenty years after Ngugi bade his famed 'farewell to English.' This sprawling 776-page magnum opus (published in Gikuyu in three installments totaling 892 pages) is probably the longest piece of prose in sub-Saharan Africa to be composed and published in an indigenous language.